Professionality of Lecturers Faculty of Educational Sciences University of Manado State - Kawulur, Ivone Viske Suharti; Mokat, J E H; Sendow, Recky (Technium Social Sciences Journal, 2021)
This study aims to describe the professionality of lecturers in providing public services at FIP Unima, in terms of the implementation of education, learning processes, research, and service as well as improvement or development of academic qualifications and competencies and to describe the supporting factors and inhibiting factors for the professionality of lecturers in providing public services. This research is a qualitative research with descriptive research method. Data collection techniques in research by conducting observations, interviews, and documentation. Data analysis uses an interactive model according to Miles and Huberman. The results of this study explain that the professionality of lecturers in carrying out their duties and obligations at FIP Unima has had the quality of attitudes contained in the knowledge and expertise in carrying out education including planning and implementing the learning process, as well as conducting assessments, but not all lecturers have increased their professionality in the field of research and service. the result of this research showing that not all FIP Unima lecturers have expertise in the fields of research and service as well as publications which are part of the tridharma of higher education. In addition, there are 11 lecturers who improve their professionality by developing academic qualifications and competencies on an ongoing basis in strata 3 (S3) education. The supporting factors for the professionality of FIP Unima lecturers are 1) Availability of LMS, 2) Availability of financial support from Unima management for the implementation of the Tridharma of Higher Education which is part of the professionality of lecturers and 3) Availability of Cooperation with various parties. Furthermore, the inhibiting factors for the application of lecturer professionality in carrying out their duties and obligations at FIP Unima are: 1) There is no systematic control of the implementation of education, research, and service as well as improvement or development of academic qualifications and lecturer competencies. 2) There are no clear rules and mechanisms regarding sanctions for lecturers who do not have high professionality